Technical And Pedagogical Innovations For Training Students At ISPITS Of Tétouan: A Procedural Simulation Model (International Journal of Environmental Sciences, 2025)
Simulation plays a crucial role in nursing education, enabling students to apply the theoretical knowledge and skills they have acquired through the use of high- and low-fidelity procedural simulators. These simulators facilitate learning by allowing students to practice procedures—primarily technical ones—without any risk to patients. Mastery of therapeutic administration is one of the fundamental technical skills that nurses must develop. While there are commercially available intradermal injection simulators, they tend to be prohibitively expensive.This study aims to integrate simulation-based learning into nursing education at the Higher Institute of Nursing Professions and Health Techniques of Tetouan (ISPITS-T) by utilizing alternative, cost-effective tools for teaching therapeutic administration. Specifically, we employed a sponge cuff, viscous gel, and chicken thighs as simulators. A total of 38 first-year general nursing students from ISPITS-T participated in the study. To evaluate the effectiveness of these proposed simulators in generating actionable knowledge in these students, we collected quantitative data through A self-administered pre- and post-test was developed to assess technical and non-technical skills related to administering drugs by injection (intradermal and subcutaneous). Pre- and post-tests were administered before and after the procedural simulation training sessions for subcutaneous and intradermal injections. They consisted of eight questions, formulated as statements reflecting the students' level of preparedness, confidence, stress level, technical accuracy, satisfaction, and perception of the educational value of the simulation activity. The Wilcoxon test was used to evaluate student performance. The results indicated statistically significant differences between pre-test and post-test scores for all evaluated items (Z values ranging from -3.569 to -5.031; p < 0.001). This demonstrates a significant improvement in student performance following the simulation sessions. Therefore, the sponge cuff, viscous gel, and chicken thighs prove to be effective and inexpensive simulators that enhance the technical skills required for therapeutic injections among nursing students.